Research Anthology on BIM and Digital Twins in Smart Cities 2022
DOI: 10.4018/978-1-6684-7548-5.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Coupling BIM and Game Engine Technologies for Construction Knowledge Enhancement

Abstract: Interactions and collaboration between parties in construction projects are often characterised by misunderstandings and poor information exchange. Game engine technologies, when employed with building information modelling (BIM), can help address these shortcomings. Quite often, the visualisation capabilities of BIM models are not explored fully partly because of their limited interactive capability. While game engines are powerful in visualisation and interactions in the gaming industry, the literature sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…At this stage, students with great research potential can be identified for potential engagement with research later. Engaging students in research is extremely important especially at Master's level given its duration is only 1 year in the UK In our case, early identification and engagement of students with the potential in research led to the publication high impacts articles at undergraduate (Abanda and Byers, 2016) and postgraduate (Abanda et al, 2020;Buhammood et al, 2020) within the duration of their programs. A major implication from this lesson is that educators will be more willing to identify and engage students in research at an early stage in the semester knowing well that it is possible for such students to deliver high impact articles while at the same time completing the other coursework components or assignments.…”
Section: Lessons Learnt and Implicationsmentioning
confidence: 82%
See 2 more Smart Citations
“…At this stage, students with great research potential can be identified for potential engagement with research later. Engaging students in research is extremely important especially at Master's level given its duration is only 1 year in the UK In our case, early identification and engagement of students with the potential in research led to the publication high impacts articles at undergraduate (Abanda and Byers, 2016) and postgraduate (Abanda et al, 2020;Buhammood et al, 2020) within the duration of their programs. A major implication from this lesson is that educators will be more willing to identify and engage students in research at an early stage in the semester knowing well that it is possible for such students to deliver high impact articles while at the same time completing the other coursework components or assignments.…”
Section: Lessons Learnt and Implicationsmentioning
confidence: 82%
“…This is done after the dissertation must have been Source(s): Author's submitted. Examples of outputs published using this method are Abanda and Byers (2016) and Buhammood et al (2020), undergraduate and postgraduate students respectively.…”
Section: Approaches Of Research-informed Teaching (Rit)mentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar das atividades colaborativas serem práticas constantes em projetos arquitetônicos, as interações e a colaboração entre as partes são frequentemente caracterizadas por mal-entendidas e a troca de informações são consideradas insuficientes e ineficazes [3], sendo que, muitas vezes, os usuários leigos não conseguem compreender as representações utilizadas pelos arquitetos e projetistas nas etapas iniciais do projeto, podendo resultar em soluções arquitetônicas que não levam em consideração suas necessidades [4]. Desta forma, a chave para esta desconstrução está em partir do reconhecimento das assimetrias de conhecimento entre os grupos socioespaciais e os técnicos, assim como evitar a tradicional imposição ou informação das tomadas de decisão por parte dos especialistas em projeto [5].…”
Section: Introductionunclassified
“…Entretanto, apesar de pesquisas confirmarem os efeitos positivos das simulações imersivas em termos de entrega de projetos de melhor qualidade por meio de uma comunicação mais aprimorada, estas tecnologias ainda não estão amplamente integradas na prática arquitetônica e algumas reformulações precisam ser feitas em relação à sua aplicação no desenvolvimento do projeto [9]. Buhammood et al [3] também afirmam que os recursos de visualização dos modelos BIM não estão sendo totalmente explorados, em parte devido à sua capacidade interativa limitada. Além disso, por se tratar de uma ferramenta que envolve programação computacional, conhecimento que geralmente foge do domínio dos projetistas pela inexperiência na área, o uso em conjunto destas tecnologias também é dificultado.…”
Section: Introductionunclassified